ANALISIS HUBUNGAN R&D DENGAN KINERJA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR PADA INDEKS KOMPAS 100 - Muhammad Rosidi, rosidi (Jurnal Publikasi Ekonomi dan Akuntansi, 2022)
This study aims to examine the relationship between R&D intensity and firm performance of the manufacturing company listed in Indonesia Stock Exchange (IDX) 2015-2017. The sample observation used were manufacturing companies listed on Kompas 100 Index 2015 to 2017 observations. This data used was obtained from Badan Pusat Statistik and Indonesian Stock Exchange. The number of samples used is 65 manufacturing companies listed on Kompas 100 index. The technical analysis is linear regression, descriptive analysis and significant test. The result of this study is R&D intensity affects on the firm performance, while leverage, growth sales, and firm size as control variables. Based n t test only R&D intensity variable who have a significant effect on firm performance. The implication of this analysis we predict that R&D activities support stabilization in financial condition of the company. We welcome future studies the continue our reseacrh aboout the effect R&D activities on financial sustainability.